2022
DOI: 10.1108/apjml-12-2021-0903
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors influencing impulse buying in live streaming shopping: a stimulus-organism-response (SOR) perspective

Abstract: PurposeBased on the stimulus-organism-response theory, this research constructs the influence of the stimulus factors of the live-streaming shopping environment on consumers' psychological situation. It then produces the research model of impulsive purchase intention.Design/methodology/approachIn this study, the online questionnaire survey method was used to survey users who participated in live-streaming shopping, and a total of 335 valid questionnaires were collected. Then SPSS and SmartPLS were used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 54 publications
5
54
0
6
Order By: Relevance
“…Prior research establishes that brand experience impacts consumers' BP (Bian and Haque, 2020;Morrison and Crane, 2007). In line with the stimulus-organism-response model, prior research shows that virtual environment design (Lin et al, 2022). Etemad-Sajadi (2016) shows that online interactive cues (like playing advergames in our research) can significantly impact patronage intention through eliciting emotional appeal and cognitive trust towards the brand.…”
Section: Hypothesis Formulationsupporting
confidence: 72%
“…Prior research establishes that brand experience impacts consumers' BP (Bian and Haque, 2020;Morrison and Crane, 2007). In line with the stimulus-organism-response model, prior research shows that virtual environment design (Lin et al, 2022). Etemad-Sajadi (2016) shows that online interactive cues (like playing advergames in our research) can significantly impact patronage intention through eliciting emotional appeal and cognitive trust towards the brand.…”
Section: Hypothesis Formulationsupporting
confidence: 72%
“…The theory has been widely applied to different consumer behavior contexts, such as retailing (Chang, Eckman, and Yan 2011), e-marketing (Kamboj et al 2018), hospitality marketing (Emir et al 2016), and tourism marketing (Rajaguru 2014). In the past decade, the S-O-R model has been widely used in influencer marketing studies to measure the impact of online influencers as stimuli of affective organisms and subsequent behavioral responses (Aw et al 2023; Gamage and Ashill 2023; Ingrassia et al 2022; Lee and Chen 2021; Lin et al 2022; Seçilmiş, Özdemir, and Kılıç 2022; Zhou et al 2021). In Table 1, we summarize some recent studies using the S-O-R model in online influencer marketing settings to illustrate why we chose to use this model to study influencers’ impact on impulsive behavior in live streaming e-commerce.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, the perceived value of an offering plays an important role in predicting customer behaviors (Ashton et al 2010;Wang 2010). Prior studies of online food marketing showed a strong association between perceived value and impulse purchase (Djafarova and Rushworth 2017;Lee and Chen 2021;Lin et al 2022;Trivedi et al 2022;Yang et al 2021). Although viewers perceived the online content delivered by the influencers to be useful (utilitarian value), socially satisfying (social value), or entertaining (hedonic value), prior studies have repeatedly observed impulse purchase of products showcased by the influencers.…”
Section: Impact Of Perceived Value On Impulse Food Purchase and Consu...mentioning
confidence: 99%
“…Xiong et al [16] found that the live streaming of agricultural products can take the livestreaming intermediary as the information link, reduce the information asymmetry through the information interaction mechanism, provide the quality endorsement for agricultural products through the reputation effect mechanism, and show the supply chain management ability to consumers through the signal transmission mechanism, thus establishing a "trinity" trust system. As an agricultural product with obvious geographical characteristics, Lin [5] believed that consumer trust under the e-commerce live broadcast mode is established and has a certain positive impact in the field of geographical indication of agricultural product purchase intention. From the study of live marketing of agricultural products and its marketing methods, the aspects involved in the study are more extensive and specific.…”
Section: Literature Reviewmentioning
confidence: 99%